Peran Peneliti dan Analis Kebijakan dalam Pembentukan Prolegnas dan RUU di Setjen DPD RI - Fuad, Zamzam Muhammad (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2017)
One of the challenges of the Secretary-General of Dewan Perwakilan Daerah Republik Indonesia (Setjen DPD RI) is to support both development of National Legislation Priority (Prolegnas) and the Bill of DPD RI. Researchers and policy analysts possess a strategic position in facing the challenge. However, researchers and policy analysts have not had clear roles, tasks, and functions yet on the making of both Prolegnas and the Bill. This study aims to provide a model of role for researchers and policy analysts on the making of both Prolegnas and the Bill in Setjen DPD RI. This study uses qualitative case study approach and aims to show that both researchers and policy analysts have each different roles. The differences can be seen from the momentum of task implementation, output, and the level of influence. This study recommends a follow-up study that will explore the role of all employees involved on the making of Prolegnas and the Bill of DPD RI